2012
DOI: 10.1007/s10534-012-9545-7
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal levels of amyloid β-peptide oligomers decrease non-transferrin-bound iron uptake and do not potentiate iron toxicity in primary hippocampal neurons

Abstract: Two major lesions are pathological hallmarks in Alzheimer's disease (AD): the presence of neurofibrillary tangles formed by intracellular aggregates of the hyperphosphorylated form of the cytoskeletal tau protein, and of senile plaques composed of extracellular aggregates of amyloid beta (Aβ) peptide. Current hypotheses regard soluble amyloid beta oligomers (AβOs) as pathological causative agents in AD. These aggregates cause significant calcium deregulation and mediate neurotoxicity by disrupting synaptic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…We used the sub-lethal AβOs concentration of 500 nM, which is deleterious to neuronal function because it inhibits long term potentiation (Wang et al, 2002; Schlenzig et al, 2012) and produces aberrations in synapse composition, shape and density (Lacor et al, 2007). Furthermore, treatment with 500 nM AβOs increases reactive oxygen species (ROS) levels (De Felice et al, 2007; Lobos et al, 2016), decreases non-transferrin-bound iron uptake (SanMartín et al, 2012b) and induces differential gene expression (Sebollela et al, 2012). Addition of 500 nM AβOs increases cytoplasmic calcium in primary hippocampal (Paula-Lima et al, 2011) and cortical neurons (Ferreira et al, 2014) and cerebellar granule cells (Sanz-Blasco et al, 2008), and results in depolarization of mitochondrial membrane potential in primary cortical neurons (Ferreira et al, 2014) and cerebellar granule cells (Sanz-Blasco et al, 2008), among other effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the sub-lethal AβOs concentration of 500 nM, which is deleterious to neuronal function because it inhibits long term potentiation (Wang et al, 2002; Schlenzig et al, 2012) and produces aberrations in synapse composition, shape and density (Lacor et al, 2007). Furthermore, treatment with 500 nM AβOs increases reactive oxygen species (ROS) levels (De Felice et al, 2007; Lobos et al, 2016), decreases non-transferrin-bound iron uptake (SanMartín et al, 2012b) and induces differential gene expression (Sebollela et al, 2012). Addition of 500 nM AβOs increases cytoplasmic calcium in primary hippocampal (Paula-Lima et al, 2011) and cortical neurons (Ferreira et al, 2014) and cerebellar granule cells (Sanz-Blasco et al, 2008), and results in depolarization of mitochondrial membrane potential in primary cortical neurons (Ferreira et al, 2014) and cerebellar granule cells (Sanz-Blasco et al, 2008), among other effects.…”
Section: Discussionmentioning
confidence: 99%
“…The Aβ 1-42 peptide was prepared as previously described, as a HFIP film (De Felice et al, 2007; Paula-Lima et al, 2011; SanMartín et al, 2012a,b; Lobos et al, 2016). This film is dissolved next in DMSO to obtain a 5 mM stock solution, which is subsequently diluted with cold phosphate buffered saline (PBS) to 100 μM and incubated overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed by the authors that the observed iron change is due to the increased amount of Aβ (Wan et al, 2011), however, it can be alternatively explained by loss-of-APP function. Aβ oligomers were shown to decrease NTBI uptake, however, the disease relevance was unclear (SanMartin et al, 2012). Recently, tau protein was found to mediate APP trafficking, and reduction of tau blocked iron export, leading to intracellular iron accumulation (Lei et al, 2012).…”
Section: Toxicity Mechanisms Of Iron Overload In Diseasesmentioning
confidence: 99%
“…Zinc +2 and Cu +2 accelerate amorphous Aβ aggregation whereas Al +3 and Fe +3 tend to promote Aβ fibril and oligomer formation (Kawahara 2005, Kawahara and Kato-Negishi 2011, Ricchelli et al 2005). SanMartín et al (2012) interpreted the elevated concentrations of Al, Cu, Fe, and Zn in human neurofibrillary tangles and senile plaques along with their in vitro acceleration of Aβ fibril and amyloid β oligomer formation as consequences of oxidative stress.…”
Section: Organ Systems and Functionmentioning
confidence: 99%